The approach of EU labour law in redressing the problems of working parents and carers - Ristovski Aleksandar; Kalamatiev Todor (Institute of Social Sciences – Center for Demographic Research, 2023)
The conflict between employment and family responsibilities, that is, private life in general, is regarded as one of the most pressing concerns of labour law over an extended period. In the context of increasing participation of women in labour markets, ageing of the population and changes in the archetypal forms of employment relationships and families, the issue of reconciling work with family life, i.e. maintaining the work-life balance, affects all social actors: workers, employers and governments. In light of this, the paper first analyses the EU policies and legislative measures related to the special protection of women in relation to pregnancy and maternity, including the right to maternity leave. Additionally, it addresses the special rights of working parents, including the right to parental leave for both men and women workers. Finally, the paper looks at the most recent EU Directive on Work-Life Balance of 2019, providing a critical review of both the newly introduced rights in the Directive, such as paternity and carers’ leave, and the already established rights of parental leave and flexible working arrangements.
Keywords: reconciliation of work with family life, pregnancy and maternity rights, rights of working parents and carers, work-life balance